AKTIVITAS ANTIMITOTIK DARI EKSTRAK KARANG LUNAK GENUS SINULARIA - Wendy Alexander Tanod; Remy E. P. Mangindaan; Magie Kapojos (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2015)
Soft coral genus Sinularia be a sources of terpenoid compounds that show efficacy in vitro cytotoxic test using cancer cell lines. The study looked at the morphological changes that occur in fungal mycelial growth of Pyricularia oryzae, such as curling effect indicating antimitotic activity. Four extracts of soft coral genus Sinularia have been examination and this is an primary test to obtain information about the soft coral genus Sinularia that used as sources of compound antimitotic. This research was conducted in several stages, ie extraction of bioactive substances, P. oryzae fungal culture test, and biological testing antimitotic activity with a qualitative assessment methods. From the examination the Sinularia 3 ethyl acetate fraction show the strongest antimitotic activity (to concentration 1,5 μg/ml). Ethyl acetate fraction was purified using column chromatography. From the examination show that fraction of ethyl acetate 1 is the best fraction because still show curling effect on concentration 0,7 μg/ml.Keywords : Antimitotic, Soft Coral, Sinularia, microtubule, Pyricularia oryzae